2016
DOI: 10.1001/jama.2016.12717
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Participation in a Medicare Bundled Payment Initiative and Payments and Quality Outcomes for Lower Extremity Joint Replacement Episodes

Abstract: IMPORTANCE Bundled Payments for Care Improvement (BPCI) is a voluntary initiative of the Centers for Medicare & Medicaid Services to test the effect of holding an entity accountable for all services provided during an episode of care on episode payments and quality of care. OBJECTIVE To evaluate whether BPCI was associated with a greater reduction in Medicare payments without loss of quality of care for lower extremity joint (primarily hip and knee) replacement episodes initiated in BPCI-participating hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
286
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(309 citation statements)
references
References 11 publications
16
286
0
1
Order By: Relevance
“…Evaluations of the first two years of the Pioneer ACO model found broadly similar results: improvements on some measures of quality performance, with no evidence of adverse effects on others (McWilliams et al 2015;Nyweide et al 2015). Similarly, evidence from the first two years of CMMI's Bundled Payments for Care Improvement initiative, found that the savings achieved under that initiative came at no cost in terms of quality of care (Dummit et al 2016). This evidence implies that APMs will be successful in improving the overall value of the care delivered, not just in reducing spending.…”
Section: Quality Performance In Alternative Payment Modelsmentioning
confidence: 89%
See 1 more Smart Citation
“…Evaluations of the first two years of the Pioneer ACO model found broadly similar results: improvements on some measures of quality performance, with no evidence of adverse effects on others (McWilliams et al 2015;Nyweide et al 2015). Similarly, evidence from the first two years of CMMI's Bundled Payments for Care Improvement initiative, found that the savings achieved under that initiative came at no cost in terms of quality of care (Dummit et al 2016). This evidence implies that APMs will be successful in improving the overall value of the care delivered, not just in reducing spending.…”
Section: Quality Performance In Alternative Payment Modelsmentioning
confidence: 89%
“…32 The lower bound of this range reflects the White (2013) that ACOs have reduced annual spending for aligned beneficiaries by 0 to 3 percent, with early evidence suggesting that ACOs start at the bottom of that range and move toward the top as they gain experience (McWilliams et al 2016;McWilliams 2016). Research examining the first two years of CMMI's smaller Pioneer ACO model found savings of a broadly similar magnitude (Nyweide et al 2015;McWilliams et al 2015), while evidence from the first two years of CMMI's Bundled Payments for Care Improvement initiative, CMMI's largest bundled payment program, found savings of around 4 percent of episode spending among participating hospitals relative to non-participating hospitals (Dummit et al 2016). …”
mentioning
confidence: 99%
“…Bundled payment for surgical procedures has been found to reduce costs without decreasing quality (Dummit, Kahvecioglu, Marrufo, & et al, 2016) and reduce inpatient costs, readmissions, and length of stay (Iorio et al). Bundled payment implementation (Hussey, Ridgely, & Rosenthal, 2011; Ridgely, De Vries, Bozic, & Hussey, 2014) and the design of bundled payment models for chronic care (O’Byrne et al, 2013) has been challenging, though a bundled payment for diabetes care in the Netherlands did lead to improved care coordination (de Bakker et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…3 The expense of post–acute care may diminish its use under cost-containment incentives. 4 Alternatively, pressure to reduce costs by reducing unnecessary readmissions may encourage its use. Our objective was to document recent trends in use of institutional post–acute care (including the 2 most common sites: skilled nursing facilities [SNFs] and inpatient rehabilitation facilities [IRFs]) and, simultaneously, hospital and post–acute care length of stay.…”
mentioning
confidence: 99%